Land Reform, Rural Development, and Poverty in the Philippines : Revisiting the Agenda - World Bank (Washington, DC, 2014)
The goal of this report is to take stock of the existing evidence on the impact of the Comprehensive Agrarian Reform Program (CARP) on poverty, to examine the current challenges that an extension of CARP would face, and to suggest directions toward achieving progress on land reform given the financial and policy constraints faced by the program. The report starts by examining the nature and relevance of the challenges that an extension of the land reform program will face. It then addresses the role of land reform in rural development and poverty reduction. The impact of agrarian reform on land markets, access to credit and, more broadly, on the competitiveness of small farms is then examined, separating the case of rice and corn lands from that of sugarcane plantations, the latter taken as an important 'case-study' of the broader plantation sector. Implications for redesigning the program are then drawn, focusing in particular on the need to more closely involve important actors in the current process of rural development. The report finally considers the institutional changes that will be required.